Manifestasi Okular dan Non Okular Sindrom Rubella Kongenital Pada Penderita Katarak Kongenital - Josiah Irma; Iwan Sovani; Maya Sari Wahyu; Feti Karfiati (Medicinus, 2018)
Background: Maternal infection with rubella in the first trimester of pregnancy result in congenital rubella syndrome (CRS). It caused blindness, deafness, congenital heart dissease and mental retardation. One of the main cause of blindness in CRS is congenital cataract. Infant affected with CRS worldwide estimated 238.000 each year and 46.000 live in South East Asia.Objective: This study aimed to looked for other ocular and non ocular manifestation from 0-11months old congenital cataract infants based on World Health Organization (WHO) CRS case definiton: suspected, clinically confirmed and labaratory confirmed.Methods:This is a retrospective observational study. We colected all data from computer base medical record, patient with congenital cataract 0-11 months old that came to Pediatric Ophthalmology unit Cicendo Eye Hospital from January 2012 until December 2013. Age, sex, laterality, axial length, cataract morphology, retinopathy pigmentary, cardiac dissorder, hearing impairment, mental dissorder and laboratory serology rubella for IgM and IgG were recorded.Results: We found ninety three patients diagnosed with CRS from congenital cataract cases. Ocular manifestation include microphthalmia in 63 eyes (33.9%), microcornea in 30 eyes (16.1%), and pigmentary retinopathy in 1 eye (0.5%) . The most common type of cataract morphology was nuclear type (49.9%.). Non-ocular manifestation include cardiac dissorder in 16 cases (17.2%), hearing impairment in 1 case (1.1%) and mental retardation in 6 cases (6.4%). Case definition based on WHO criteria were 93 cases (100%) for suspected, 20 cases (25.8%) for clinically confirmed and 15 cases (42,8%) for laboratory confirmed.Conclusion: Ocular manifestation for CRS in congenital cataract 0-11 months old were microphthalmia, microcornea, pigmentary retinopathy. Other manifestation found were cardiac disorder, hearing impairment and mental retardation.